PENINGKATAN PARTISIPASI MASYARAKAT DALAM PROSES PEMBENTUKAN PERATURAN DAERAH DI KOTA PEKANBARU - Isril Isril; Zulfa Harirah; Rury Febrina; Sofyan Hadi (ABDI MAKARTI, 2022)
Basically, the preparation of regional regulations departs from the expectation of the realization of quality public services. One of the steps that can be taken is to bring input and aspirations from the community. The Government can capture the aspirations of the community as the parties affected by the presence of public policies. This service is carried out in Pekanbaru City, precisely in Marpoyan Damai and Senapelan District. This service activity also emphasizes the importance of community involvement in making regional regulations. Therefore, this service is carried out in the context of strengthening community participation in the formation of regional regulations. This activity is carried out using presentation and discussion methods to provide understanding to the community regarding three things, namely the concept of participation, participation channels and solutions in dealing with participation constraints. The results of this service activity further add to the public's insight regarding the technical delivery of aspirations. Through this service activity, the community gains reinforcement regarding ways that can be done to pass the proposal. Communities need to know specific ways to convey aspirations, including making superior programs, conveying aspirations in forums and synchronizing proposals with the sub-district agenda.